OwlFood (Delivery Service) / Nur Izzati Auni Nor Amri - Nur Izzati Auni, Nor Amri (2020)
Our Mission Owlfood is a new online food delivery service based in Seri Iskandar, Perak. We began our business in 2019 and looking forward to be the customer's first choice of food delivery service in Malaysia. Our main mission is to connect consumers to a range of eateries and restaurants around Seri Iskandar and delivers what they ordered straight to their doorstep by giving a fast delivery service to gives satisfaction and inner contentment to keep their loyalty to our service. The Company and Management Owlfood business operated by NIANA.CO company in 2019. NIANA.CO is a partnership business owned by Nur Izzati Auni Binti Nor Amri and Muhamad Haizad Bin Hashim. The idea of doing delivery service in Seri Iskandar popped into the head when there's still no proper and official delivery service there. For now, we only have 5 manpower working in the office and as delivery riders in order to make the business work. Our Product We offer delivery service in Seri Iskandar, Bota and Tronoh from a range of restaurants in Seri Iskandar. Our service available from early in the morning until late midnight which is from 8 am to 3 am. The normal delivery fee is only between RM5-RM7 ringgit which is cheap and affordable for everyone. However, we always offer a promotion for our loyal customers. Our Competitive Advantages Malaysia has already had two well-known delivery services throughout all-state. So our company has to be prepared to compete with the other company if their services entered Seri Iskandar. Our service has a slight difference from the others. We offer live chat sessions for disabled people in order to make our service accessible to everyone. Next, we offer 50% off and giving out gifts for our loyal customers on their birthday.